1999
DOI: 10.1128/iai.67.3.1481-1492.1999
|View full text |Cite
|
Sign up to set email alerts
|

Cystic Fibrosis Transmembrane Conductance Regulator-Mediated Corneal Epithelial Cell Ingestion of Pseudomonas aeruginosa Is a Key Component in the Pathogenesis of Experimental Murine Keratitis

Abstract: Previous findings indicate that the cystic fibrosis transmembrane conductance regulator (CFTR) is a ligand for Pseudomonas aeruginosa ingestion into respiratory epithelial cells. In experimental murine keratitis, P. aeruginosa enters corneal epithelial cells. We determined the importance of CFTR-mediated uptake of P. aeruginosa by corneal cells in experimental eye infections. Entry of noncytotoxic (exoU) P. aeruginosa into human and rabbit corneal cell cultures was inhibited with monoclonal antibodies and pept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(21 citation statements)
references
References 36 publications
0
21
0
Order By: Relevance
“…Experiments using epithelial cell lines carrying either the wildtype or ∆F508 variants of CFTR indicated that the internalization of P. aeruginosa was reduced when mutant but not wildtype CFTR was expressed, suggesting that CFTR mutations may promote P. aeruginosa infection [44]. In contrast, CFTR-dependent internalization of P. aeruginosa in corneal epithelial cells is necessary for this bacterium to cause keratitis [48][49][50]. Similarly, in Salmonella enterica serovar Typhi, entry into intestinal epithelial cells is also mediated by CFTR, and it has been documented that CF patients possessing mutant forms of this protein might be protected from contracting typhoid fever [51].…”
Section: Animal and Plant Receptors Recognize Lps And Mount An Immunementioning
confidence: 99%
“…Experiments using epithelial cell lines carrying either the wildtype or ∆F508 variants of CFTR indicated that the internalization of P. aeruginosa was reduced when mutant but not wildtype CFTR was expressed, suggesting that CFTR mutations may promote P. aeruginosa infection [44]. In contrast, CFTR-dependent internalization of P. aeruginosa in corneal epithelial cells is necessary for this bacterium to cause keratitis [48][49][50]. Similarly, in Salmonella enterica serovar Typhi, entry into intestinal epithelial cells is also mediated by CFTR, and it has been documented that CF patients possessing mutant forms of this protein might be protected from contracting typhoid fever [51].…”
Section: Animal and Plant Receptors Recognize Lps And Mount An Immunementioning
confidence: 99%
“…Primary cultures of human epithelial corneal cells were established from corneal rims prepared and cultured in flasks as described by Zaidi et al 31 Cells were seeded at 2 3 10 5 cells per well in 24-well plates and after 18 hours exposed to a 1:20 or 1:10 dilution of the cell-free, sterile supernatant from S. aureus strains LAC, LACDPVL, MW2, or MW2DPVL grown overnight at 378C in YCP broth. Aliquots from the wells were collected every 5 minutes and lactate dehydrogenase (LDH) release determined by a commercially available assay (Tox-7 in vitro cytotoxicity assay; Sigma, St. Louis, MO).…”
Section: Lactate Dehydrogenase Assay For Corneal Cell Cytotoxicitymentioning
confidence: 99%
“…The epithelial cells were grown in 96-well tissue culture plates as described 24 and incubated with 0, 0.5, 2, or 5 mM CD for 30 minutes, then infected for 3 hours with various P. aeruginosa strains at a multiplicity of infection of ϳ10:1. In brief, approximately 10 6 CFU of P. aeruginosa was added to monolayers of 10 5 cultured corneal cells.…”
Section: Cell Culture and In Vitro Infection Of Cellsmentioning
confidence: 99%
“…To determine the internalized colony-forming units, gentamicin-exclusion assays were used as described elsewhere. 21,24,[35][36][37] Three-hundred micrograms gentamicin per milliliter was added to the infected epithelial cell cultures to kill extracellular bacteria. After 1 hour of exposure to the antibiotic, the cells were washed, and intracellular bacteria were released from them by lysis with 0.5% Triton X-100, diluted, and plated for bacterial enumeration.…”
Section: Cell Culture and In Vitro Infection Of Cellsmentioning
confidence: 99%
See 1 more Smart Citation